Identification of p72 epitopes of African swine fever virus and preliminary application - Miao, Chun; Yang, Sicheng; Shao, Junjun; Zhou, Guangqing; Ma, Yunyun; Wen, Shenghui; Hou, Zhuo; Peng, Decai; Guo, HuiChen; Liu, Wei; Chang, Huiyun (Frontiers in Microbiology, 2023)
African swine fever virus (ASFV) causes a highly lethal hemorrhagic viral disease (ASF) of pigs that results in serious losses in China and elsewhere. The development of a vaccine and diagnosis technology for ASFV is essential to prevent and control the spread of ASF. The p72 protein of ASFV is highly immunogenic and reactive, and is a dominant antigen in ASF vaccine and diagnostic research. In this study, 17 p72 monoclonal antibodies (mAbs) were generated. Epitope mapping by a series of overlapping peptides expressed in Escherichia coli showed that these mAbs recognized a total of seven (1–7) linear B cell epitopes. These mAbs did not show significant neutralizing activity. Epitopes 1 (249HKPHQSKPIL258), 2 (69PVGFEYENKV77), 5 (195VNGNSLDEYSS205), and 7 (223GYKHLVGQEV233) are novel. Sequence alignment analysis revealed that the identified epitopes were highly conserved among 27 ASFV strains from nine genotypes. Preliminary screening using known positive and negative sera indicated the diagnostic potential of mAb-2B8D7. The results provide new insights into the antigenic regions of ASFV p72 and will inform the diagnosis of ASFV.